The associations of obesity phenotypes with the risk of hypertension and its transitions among middle-aged and older Chinese adults - Ziyue Sheng; Shang Lou; Jin Cao; Weidi Sun; Yaojia Shen; Yunhan Xu; Ziyang Ren; Wen Liu; Qian Yi; Peige Song (Epidemiology and Health, 2023)
OBJECTIVES This study aimed to investigate the associations of obesity phenotypes with hypertension stages, phenotypes, and transitions among middle-aged and older Chinese. METHODS Using the 2011-2015 waves of the China Health and Retirement Longitudinal Study, we conducted a cross-sectional analysis included 9,015 subjects and a longitudinal analysis included 4,961 subjects, with 4,872 having full data on the hypertension stage and 4,784 having full data on the hypertension phenotype. Based on body mass index and waist circumstance, subjects were categorized into 4 mutually exclusive obesity phenotypes: normal weight with no central obesity (NWNCO), abnormal weight with no central obesity (AWNCO), normal weight with central obesity (NWCO), and abnormal weight with central obesity (AWCO). Hypertension stages were classified into normotension, pre-hypertension, stage 1 hypertension, and stage 2 hypertension. Hypertension phenotypes were categorized as normotension, pre-hypertension, isolated systolic hypertension (ISH), isolated diastolic hypertension (IDH), and systolic-diastolic hypertension (SDH). The association between obesity phenotypes and hypertension was estimated by logistic regression. A comparison between different sexes was conducted by testing the interaction effect of sex. RESULTS NWCO was associated with normal→stage 2 (odds ratio [OR], 1.95; 95% confidence interval [CI], 1.11 to 3.42), maintained stage 1 (OR, 1.62; 95% CI, 1.14 to 2.29), and normal→ISH (OR, 1.39; 95% CI, 1.05 to 1.85). AWCO was associated with normal→stage 1 (OR, 1.75; 95% CI, 1.40 to 2.19), maintained stage 1 (OR, 2.77; 95% CI, 2.06 to 3.72), maintained stage 2 (OR, 2.80; 95% CI, 1.50 to 5.25), normal→ISH (OR, 1.56; 95% CI, 1.20 to 2.02), and normal→SDH (OR, 2.54; 95% CI, 1.72 to 3.75). An interaction effect of sex existed in the association between obesity phenotypes and hypertension stages. CONCLUSIONS This study highlights the importance of various obesity phenotypes and sex differences in hypertension progression. Tailored interventions for different obesity phenotypes may be warranted in hypertension management, taking into account sex-specific differences to improve outcomes.